2014
DOI: 10.1177/026248931403300502
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made High Density PLA Foam Sheets - Strategies to Improve the Mechanical Properties

Abstract: In this study, different strategies to improve the mechanical properties of physically foamed high density polylactic acid (PLA) sheets were examined to produce PLA foam sheets with tailor-made mechanical properties. The first part was the determination of the influence of the blending of PLA with polybutylene succinate (PBS) on the properties of the high density foam sheets. Additionally, the influence of the PBS on the rheological properties was investigated with a cone plate rheometer. The second part was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Consequently, only a few reports were done, mainly with azodicarbonamide (ADC) [ 43 , 59 , 60 , 84 , 99 , 110 ]. Also, nitrogen is rarely applied as a blowing agent for PLA and rather less expansion was achieved [ 61 ]. Another work reports the use of a combination of CO 2 and nitrogen resulting in foamed sheets with densities down to 350 kg/m 3 [ 54 ].…”
Section: Processesmentioning
confidence: 99%
“…Consequently, only a few reports were done, mainly with azodicarbonamide (ADC) [ 43 , 59 , 60 , 84 , 99 , 110 ]. Also, nitrogen is rarely applied as a blowing agent for PLA and rather less expansion was achieved [ 61 ]. Another work reports the use of a combination of CO 2 and nitrogen resulting in foamed sheets with densities down to 350 kg/m 3 [ 54 ].…”
Section: Processesmentioning
confidence: 99%
“…To demonstrate this, they compared the tensile strength and bulk densities of composite foams made from amorphous PLA mixed with plain cellulose fibers and acetylated cellulose fillers at varying concentrations. The foams were made using CO 2 gas as blowing agent for 6 h at a temperature and pressure range of 60 °C and (12)(13)(14)(15)(16)(17)(18)(19)(20) MPa respectively in the batch process. Results showed that while the foams made with acetylated cellulose gave higher bulk density with improved interfacial properties and tensile strength for up to 9 wt.% filler loading, the foams made with plain unfunctionalized cellulose fibers had a morphology with smaller average cell sizes and exhibited higher flexibility and toughness.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Using the extrusion foaming process with CO 2 and N 2 gas as a blowing agent, the mechanical properties of plain PLA foams were compared with those reinforced with joncryl chain extender. From the results, it was observed that the foams with chain extender inclusion showed increased elongation and overall improved tensile mechanical properties compared to foams without the chain extender 14 . Although PLA is a bio-based polymer with good processability it is slightly weak in toughness and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous manufacturing of low-density foamed thermoplastic sheets has unremittingly remained to be a big challenge for many manufacturers despite the initial breakthroughs that have been accomplished in the last two decades [1][2][3][4][5][6][7]. Numerous researchers and diverse inter-disciplinary industries have been very active in the field of extrusion foaming in the last few years, primarily because it allows them to manufacture thermoplastic foams continuously [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%